Polish Government-in-Exile and the Political Transformation of the Polish State in 1989-1991 - Alberska, Małgorzata (Roczniki Nauk Społecznych, 2025)
The goal of the article is to analyse the influence that the political transformation had on attitudes, decision-making and actions of Polish refugees’ environments, especially those associated with Polish government-in-exile. The article describes how the process of political transformation affected the attitudes of the politicians working in the government-in-exile towards the Polish state government, and how it ended the duality of Polish government. The main research questions are: How the Polish government-in-exile judged the events of 1989 in accordance with its own main goal? What criteria were used to judge these events? Why were there differences between the actions taken by the President with his government and those of the National Council? During the research on the topic of this article, elements of the descriptive method were used alongside the analysis of archival sources.